2021
DOI: 10.1177/02654075211033341
|View full text |Cite
|
Sign up to set email alerts
|

Successful negotiation of goal conflict between romantic partners predicts better goal outcomes during COVID-19: A mixed methods study

Abstract: When romantic partners’ personal goals conflict, this can negatively affect personal goal outcomes, such as progress. In a concurrent mixed methods study, we investigated whether goal conflict and negation of goal conflict were associated with goal outcomes (progress, confidence, motivation) and what strategies partners used during the COVID-19 pandemic to negotiate goal conflict. Survey participants ( n = 200) completed a daily diary for a week and weekly longitudinal reports for a month and interview partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…We use Karney and Bradbury’s (1995) vulnerability-stress-adaptation (VSA) model as adapted by Pietromonaco and Overall (2021) to the COVID-19 context to further categorize and understand these themes. This model has been successfully used in multiple COVID-19 and close relationship studies that were ultimately included here (e.g., Fleming & Franzese, 2021 ; Gresham et al, 2021 ; Holmberg et al, 2021 ; Vowels et al, 2021 ). Using family and relationship theory, this adapted VSA model proposes that (1) external stress (such as COVID-19 and its attendant regulations, change in job status, isolation, etc.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…We use Karney and Bradbury’s (1995) vulnerability-stress-adaptation (VSA) model as adapted by Pietromonaco and Overall (2021) to the COVID-19 context to further categorize and understand these themes. This model has been successfully used in multiple COVID-19 and close relationship studies that were ultimately included here (e.g., Fleming & Franzese, 2021 ; Gresham et al, 2021 ; Holmberg et al, 2021 ; Vowels et al, 2021 ). Using family and relationship theory, this adapted VSA model proposes that (1) external stress (such as COVID-19 and its attendant regulations, change in job status, isolation, etc.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…In one study conducted over a 10-day period where college students recorded their daily relational experiences, amount of daily conflict was positively related to COVID-19-related anxiety and inversely related to end-of-day optimism ( Merolla et al, 2021 ). At times when goal conflict with a romantic partner was higher, individuals reported that their goals were impacted by COVID-19 more than when goal conflict was lower ( Vowels et al, 2021 ). Vowels et al (2021) utilized a mixed-methods design and identified several specific methods for managing conflict during the pandemic, including: respectful communication, talking about it, focusing on emotional needs, focusing on practical solutions, taking a timeout, and avoidance.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Such support, when perceived by the recipient as being effective and responsive, can in turn lead to immediate and long-term thriving outcomes. To date, only a few studies have tested portions of this theoretical framework (Feeney et al, 2017;Tomlinson et al, 2016;Vowels & Carnelley, 2021;Vowels et al, 2022). Additional research is necessary to understand factors that may be associated with the model components.…”
Section: Thriving Through Relationshipsmentioning
confidence: 99%
“…Research shows that goal conflict has been associated with lower personal well-being, relationship quality and commitment (Gere & Impett, 2018;Gere & Schimmack, 2013;Gere et al, 2011;Kelley & Thibaut, 1978;Righetti et al, 2016;Rusbult & Van Lange, 2003), and negatively associated with different stages of the positive support process in a relationship: openness to receiving support from a partner (Righetti et al, 2014), perceived partner support (Vowels & Carnelley, 2021), and providing support toward a partner's goals (Feeney et al, 2013(Feeney et al, , 2017Hui et al, 2014). This may have serious implications for goal progress and achievement, as people are also less likely to make progress toward goals that are non-harmonious for their relationships (Gere & Schimmack, 2013;Gere et al, 2011;Vowels et al, 2022). Recent research showed that people were more likely to devalue or stop pursuing a goal (Gere & Impett, 2018) and reported less motivation toward and commitment to a goal (Vowels et al, 2022) if it was in conflict with their partner's goals.…”
Section: Non-harmonious Goals or Opportunities In Romantic Relationshipsmentioning
confidence: 99%